Evaluation of the relationship between land use and surface water quality in Seberang Perai Selatan, Penang, Malaysia - A., Shamshad (2006)
Watershed hydrology depends on the land use type, climatic condition and soil characteristics. The present study was carried out to use catchments based approach to examine possible statistical and spatial relationships of land use on the quantity and quality of surface water. Water quality tests were carried out in laboratory for samples collected at four locations. These included biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), total nitrogen, total phosphorus and pH. Water quality is examined spatially and statically. ArcView 3.2 was used to prepare land use map of catchments for the water sampling stations in Seberang Perai. The results showed that there is a significant relationship between land use and river water quality with most parameters. The modeling results further showed that expansion of urban land and agriculture are likely to lead to soil erosion, and deterioration of water quality.